Carcass traits and meat quality of Nellore cattle fed different non-fiber carbohydrates sources associated with crude glycerin - Favaro, V. R. [UNESP]; Ezequiel, J. M.B. [UNESP]; Almeida, M. T.C. [UNESP]; D'Aurea, A. P. [UNESP]; Paschoaloto, J. R. [UNESP]; Van Cleef, E. H.C.B. [UNESP]; Carvalho, V. B. [UNESP]; Junqueira, N. B. [UNESP] (Elsevier, 2016)
Crude glycerin, a potential energy source for ruminant animals, has been evaluated, mainly, in diets with high starch content. However, a limit number of studies have evaluated the inclusion of crude glycerin in low starch diets. This study aimed to evaluate the effects of the association of crude glycerin with corn grain or citrus pulp on carcass traits and meat quality of Nellore bulls (n=30, 402±31 kg initial weight). The treatment consisted of: CON=control, without crude glycerin; CG10=10% of crude glycerin and corn grain; CG15=15% of crude glycerin and corn grain; CP10=10% of crude glycerin and citrus pulp; CP15=15% of crude glycerin and citrus pulp. The performance parameters and carcass traits were not affected by treatments (P>0.05). The inclusion of crude glycerin decreased yellow color intensity and increased fatty acids pentadecanoic and heptadecenoic in meat (P<0.05), without affecting neither the concentration of polyunsaturated fatty acids nor the relationship of saturated and unsaturated fatty acids. The association of crude glycerin with corn or citrus pulp has no adverse effects on carcass characteristics and meat quality.
Keywords: by-products; carcass; fatty acids; glycerol; ruminant